Aplicación del Modelo Integrado de Desarrollo (BIM) en el Diseño de Proyectos para Oficina Abierta - Tristancho Ortiz, Julián Alfonso; Contreras Bravo, Leonardo Emiro; Vargas Tamayo, Luis Fernando (Ingeniería, 2011)
Building Information Modeling (BIM) is a process where the geometric information (size and location) generated in a conventional CAD system is integrated with the cost, planning and construction information for architectural projects. The development of applications BIM has undergone significant development since the late 1990s. The decrease in costs of CAD systems, has allowed this design methodology to be expanded to other areas of engineering and construction. This article provides a brief description for a BIM method and how it was implemented in a new software called OffiCAD. This software is integrated to a commercial CAD system that allows full management of design projects in modular furniture systems (also known as open plan projects). OffiCAD integrates information of geometric design of CAD system, with information on product database for quotation, visualization with surface finishes and production requirements. In addition, it has a series of intelligent systems for referencing, verification and correction of design errors.